Color-tunable emission from violet-blue to pure-blue based on 5, 9-disubstituted pyrene derivatives via engineering of aryl-side groups. Issue 30 (15th July 2022) - Xie, Fuli; Yang, Xilin; Jin, Pengcheng; Wang, Xiao-Tian; Ran, Huijuan; Zheng, Rong; Lei, Zheng; Zhang, Hailu; Su, Shi-Jian; Hu, Jian-Yong
Abstract : By attaching a few kinds of two aryl-side groups into pyrene core at 5, 9-positions, five pyrene-based color-tunable blue emitters have been developed for highly efficient nondoped and doped blue OLEDs. Abstract : It is especially necessary to explore the influence of side groups linked to the pyrene core on the photophysical properties for constructing efficient pyrene-based blue-emitting materials. In this study, a series of new aromatically 5, 9-disubstituted pyrene derivatives (Py-BBz, Py-B2Na, Py-B9Ph, Py-B2Ph and Py-B2An ) were designed and synthesized by integrating a few kinds of aryl-side groups into 5, 9-positions of the pyrene core adopting the Suzuki–Miyaura cross-coupling reaction. Theoretical calculations implied that the electronic coupling between the aryl-side group and the pyrene core was significantly influenced by the size and linking position of the side group, resulting in distinct photo-physical features. These newly developed compounds exhibited color-tunable emission from violet-blue (409 nm, Py-BBz ) to pure-blue (465 nm, Py-B2An ) along with the increasing size of the aryl-side group. The electroluminescence (EL) performances of nondoped and doped devices based on these compounds were fully investigated. The representative of the nondoped device based on Py-B2Ph exhibits a prominent EL performance with a pure-blue emission (EL: 459 nm; CIE xy : 0.146, 0.128) and a maximum EQE close to 6.0%. Interestingly, the EL emission of the Py-B2An -based nondoped device was nearly extended to the white emission region with CIE coordinates of (0.307, 0.452). On the other hand, the CBP-based doped device using Py-BBz as a dopant displayed a violet-blue emission with CIE coordinates of (0.152, 0.042) and an appreciable maximum EQE (3.3%) superior to that of most reported violet-blue OLEDs. The results indicated that the functionalization of the pyrene core at 5, 9-positions with suitable aryl-side groups can easily control the emission color and also provide valuable information for constructing desired blue OLEDs.